2022
DOI: 10.1177/19427751221087731
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive School Leadership in Developing Context: What Are the Levers of Change?

Abstract: In developing sub-Saharan Africa, a region, that is, in the early stages of implementing inclusive education, there is limited discussion on inclusive leadership modules for training leaders. The qualitative study presented in this paper attempted to fill this knowledge gap by considering school leaders’ contributions to implementing inclusive education for students with disabilities. The paper identifies the challenges faced by schools and the initiatives they have implemented to promote inclusive education. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 62 publications
(168 reference statements)
1
17
0
1
Order By: Relevance
“…Despite the existence of intra‐school collaboration, it was absent among the study participants. This finding is partly consistent with previous studies, which reported poor collaboration between teachers working with children with disabilities in the UAE (Alghazo & Alkhazaleh, 2021) and other contexts (Kuhl et al., 2015; Opoku, 2022). In this study context, it was evident that, because the children were studying across schools, it would be beneficial for the participants to communicate or share ideas about best teaching practices.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the existence of intra‐school collaboration, it was absent among the study participants. This finding is partly consistent with previous studies, which reported poor collaboration between teachers working with children with disabilities in the UAE (Alghazo & Alkhazaleh, 2021) and other contexts (Kuhl et al., 2015; Opoku, 2022). In this study context, it was evident that, because the children were studying across schools, it would be beneficial for the participants to communicate or share ideas about best teaching practices.…”
Section: Discussionsupporting
confidence: 92%
“…In practising inclusive education, resources have consistently been reported as inadequate (Hajj Ali & Opoku, 2023), burdening teachers in classrooms. Thus, as a result of the scarcity of resources for the successful practice of inclusive education, innovations such as assigning stakeholders to offer one-onone support to students with disabilities may be needed to advance classroom practices (Opoku, 2022). In the UAE context, understanding of disability is also lacking (Gaad, 2010).…”
Section: T H Eor Et Ica L F R a M Ewor Kmentioning
confidence: 99%
“…Moreover, teachers’ perception of the implementation of IE has been negative because they feel unqualified and unsupported to teach all students in one classroom (Ameteppee & Anastasiou, 2015; Nketsia, 2018; Nketsia & Saloviita, 2013). The ineffectiveness of IE practices raises two critical issues: (a) the actual implementation of IE policy (Ameteppee & Anastasiou, 2015; Nketsia, 2018; Nketsia & Saloviita, 2013; Opoku, 2016; Singal et al, 2015) and (b) the quality of teacher training offered in schools (Nketsia, 2018; Nketsia & Saloviita, 2013; Opoku, 2016, 2021, 2022; Opoku et al, 2022). Because teacher education is vital to the success of GATE (Merrotsy, 2015; Plunkett & Kronborg, 2011), exploring the attitudes and confidence levels of future teachers toward GATE in Ghana is essential.…”
Section: Introductionmentioning
confidence: 99%